PENDIDIKAN MORAL ANAK USIA DINI DALAM PERSFEKTIF ONTOLOGI, EPISTIMOLOGI, DAN AKSIOLOGI - Harmalis Harmalis; Eko Kuntarto; Titin Kusayang (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This article aims to analyze the concept of early childhood moral education from the perspective of ontology, epistemology, and axiology, using the literature study method. Moral values, morals and character are aimed at children aged zero to six years so that children have provisions that will be passed throughout their lives. Furthermore, based on the point of view of epistemology. that in inculcating moral values in early childhood can come from two elements, first, sourced from family education, namely by using the methods of storytelling, playing, discussing and field trips. Then the second element of pre-school education, namely the teacher has a role in instilling moral values in early childhood, using the methods of singing, rhyming, outbound, role playing and others. And based on the axiological point of view that ethics and aesthetics are two very important things to consider in instilling moral values in early childhood. Ethics are matters relating to the norms of decency and the good and bad of human behaviour, while aesthetics are matters relating to the experience of beauty possessed by humans.